2016
DOI: 10.1111/cpr.12299
|View full text |Cite
|
Sign up to set email alerts
|

Naturally occurring compounds acting as potent anti‐metastatic agents and their suppressing effects on Hedgehog and WNT/β‐catenin signalling pathways

Abstract: Despite numerous remarkable achievements in the field of anti-cancer therapy, tumour relapse and metastasis still remain major obstacles in improvement of overall cancer survival, which may be at least partially owing to epithelial-mesenchymal transition (EMT). Multiple signalling pathways have been identified in EMT; however, it appears that the role of the Hedgehog and WNT/β-catenin pathways are more prominent than others. These are well-known preserved intracellular regulatory pathways of different cellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 113 publications
(190 reference statements)
0
12
0
Order By: Relevance
“…Wnt/β‐catenin signaling pathway has been reported to play a crucial role in multiple aspects of tumor progression, including NSCLC (Han et al, ; Seto et al, ; Tang et al, ). In addition, it has been known that Wnt/β‐catenin signaling pathway is involved in cancer invasion and metastasis (Farahmand, Darvishi, Majidzadeh‐A, & Ansari, ; Rong, Zhao, & Lu, ). For example, overexpressing lncRNA FOXD2‐AS1 can promote NSCLC progression through activating Wnt/β‐catenin signaling (Rong et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Wnt/β‐catenin signaling pathway has been reported to play a crucial role in multiple aspects of tumor progression, including NSCLC (Han et al, ; Seto et al, ; Tang et al, ). In addition, it has been known that Wnt/β‐catenin signaling pathway is involved in cancer invasion and metastasis (Farahmand, Darvishi, Majidzadeh‐A, & Ansari, ; Rong, Zhao, & Lu, ). For example, overexpressing lncRNA FOXD2‐AS1 can promote NSCLC progression through activating Wnt/β‐catenin signaling (Rong et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, we revealed that WNT signalling genes were downregulated in the IC rat model 13 . The WNT signalling pathway is known to modulate tissue fibrosis and associated EMT processes 21 . Thus, we further investigated the association of fibrosis with WNT signalling cascades in IC/BPS patients.…”
Section: Discussionmentioning
confidence: 99%
“…1 ). According to current researches, deregulation of the Wnt signaling pathway is related to tumor propagation, invasion, and development of resistance to anticancer agents which steer tumors toward a malignant form of progression, and ultimately leading to poor prognosis of overall survival [ 6 , 7 ]. Interestingly, recent findings in TNBC tumors have elucidated the crosstalk between the Wnt pathway and multiple growth factors and developmental signaling pathways and β-catenin as a main downstream effector of the pathway at multiple levels [ 8 ].…”
Section: Introductionmentioning
confidence: 99%